2012
DOI: 10.1080/15533174.2012.684255
|View full text |Cite
|
Sign up to set email alerts
|

A Green and Simple Route for the Controlled-Size Synthesis of Gold Nanoparticles Using Preyssler Heteropolyacid

Abstract: The authors describe a facile procedure for size-controlled synthesis of gold nanoparticles based on the reduction of Au 3+ (HAuCl 4 ) using Preyssler heteropolyacid (H 14 [NaP 5 W 30 O 110 ]) under UV irradiation. Preyssler plays the role of green reducing agent and also efficient stabilizer. This method allows the synthesis of uniform hexagonal nanoparticles with an average size that is tunable between 1.35 and 86.7 nm by varying the gold ion concentration, molar ratio of gold ion to Preyssler, and Propan-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In the past decade, the use of heteropolyacids (HPAs) and related polyoxometalate compounds in the structure of catalysts has been employed in many selective transformations of organic substances . The supported HPA catalysts have several advantages, such as strong Brønsted acidity, higher stability, low toxicity and high catalytic activity, which make them economically and environmentally attractive in studying the catalytic process …”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, the use of heteropolyacids (HPAs) and related polyoxometalate compounds in the structure of catalysts has been employed in many selective transformations of organic substances . The supported HPA catalysts have several advantages, such as strong Brønsted acidity, higher stability, low toxicity and high catalytic activity, which make them economically and environmentally attractive in studying the catalytic process …”
Section: Introductionmentioning
confidence: 99%
“…In our previous works, Preyssler acid [34][35][36], molybdophosphoric acid [37] and vanadium-substituted mixed addenda (H 3+x [PMo 12-x V x O 40 ], (x=0-3)) [38] were introduced as remarkable reducing agents and effective stabilizers for the synthesis of gold nanostructures. It has been found that molybdophosphoric acid (H 3 [PMO 12 O 40 ], HPMo) has a high oxidation potential and it is an effective POM in the size controllable synthesis of Au NPs.…”
Section: Introductionmentioning
confidence: 99%
“…According to the importance of chitosan as an adsorbent, Tanhaei et al recently introduced a novel HPAs grafted magnetic chitosan composite for the adsorption of methyl orange. The Preyssler acid (H 14 [NaP 5 W 30 O 110 ]) was used as a type of HPAs with high hydrolytic (pH 2–12) and thermal stability, non‐corrosiveness, reusability and greenness properties .…”
Section: Introductionmentioning
confidence: 99%